2014
DOI: 10.1097/inf.0b013e3182a743c7
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Piperacillin/Tazobactam in Critically Ill Young Children

Abstract: These are the first pharmacokinetic data of piperacillin/tazobactam (piperacillin component) in critically ill pediatric patients (1-6 years of age). Based on these data, 100 mg/kg q6h as a 3-hour infusion and 400 mg/kg continuous infusion were the only regimens to provide optimal PTA at the Clinical Laboratory Standards Institute breakpoint of 16 μg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
84
6
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(107 citation statements)
references
References 32 publications
15
84
6
2
Order By: Relevance
“…43 Despite increasing appreciation of this phenomenon, scarce data are available in children receiving β-lactam antibiotics. 14,40,44 In our study population clearance values higher than expected were observed in some patients with observed individual piperacillin clearances up to 0.35 L/h/kg. We hypothesize that such an apparent variation in clearance results from an increase in renal blood flow, leading to hyperfiltration in those patients with sepsis.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…43 Despite increasing appreciation of this phenomenon, scarce data are available in children receiving β-lactam antibiotics. 14,40,44 In our study population clearance values higher than expected were observed in some patients with observed individual piperacillin clearances up to 0.35 L/h/kg. We hypothesize that such an apparent variation in clearance results from an increase in renal blood flow, leading to hyperfiltration in those patients with sepsis.…”
Section: Discussionmentioning
confidence: 90%
“…14 These findings of underdosing are consistent with previously reported exposure data in critically ill children of the same age. 14,15 For the treatment of Pseudomonas infections, no clear-cut fT>CT target values are available for tazobactam, in combination with piperacillin. Therefore, we performed a PTA analysis appraising different targets (20-60-80% fT>CT) (Figure S1, S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A complete review of experience with these dosing strategies in adults is beyond the scope of this report. While adoption of these dosing strategies has become increasingly common in the adult population, there remain limited data in children regarding efficacy, safety, and prevalence [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%